Coleópteros acuáticos y semiacuáticos del Parque Provincial Ernesto Tornquist (Provincia de Buenos Aires, Argentina) Aquatic and semiaquatic Coleoptera from Ernesto Tornquist Provincial Park (Buenos Aires Province, Argentina) - Liliana A. Fernández; Patricia L. M. Torres; Mariano C. Michat; Sylvia Fischer; Adriana Oliva; Axel O. Bachmann (Revista de la Sociedad Entomológica Argentina, 2010)
Se presenta el primer relevamiento de coleópteros acuáticos y semiacuáticos del Parque Provincial Ernesto Tornquist. El material entomológico estudiado se obtuvo durante las campañas de recolección de insectos acuáticos, realizadas entre los años 2005 y 2007, en las cuatro estaciones del año. Los ambientes estudiados fueron los arroyos Ventana, El Loro, Sauce Grande y dos charcos temporarios. Se identificaron en total 5.200 ejemplares pertenecientes a 9 familias, 20 géneros y 34 especies. Se brinda el listado de las especies y su distribución en la Argentina. Se citan, por primera vez para el parque, 23 especies y por primera vez para la Provincia de Buenos Aires: Austrelmis sp. e Hydrochus stolpi Germain. We present the results of the first survey on the aquatic and semiaquatic water beetles from the Ernesto Tornquist Provincial Park. The material was obtained from several quantitative samplings of aquatic insects covering all seasons from 2005 to 2007. The surveyed habitats were the Ventana, El Loro and Sauce Grande streams and two rain pools. A total of 5,200 specimens belonging to 9 families, 20 genera and 34 species of Coleoptera were identified. A list of the species known to occur in the park along with their distributional data in Argentina is presented. Twenty-three species are cited from the park for the first time. Austrelmis sp. and Hydrochus stolpi Germain are recorded for the first time from Buenos Aires Province.